Behavioral Risk Factors in Prevention of Hypertension Among Adolescent - Berliana, Novi; Listiawaty, Renny (Universitas STRADA Indonesia, 2020)
Data from the World Health Organization (WHO) in 2015 showed that around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world are diagnosed with hypertension. The number of people with hypertension continues to increase every year, it is estimated that by 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that each year 9.4 million people die from hypertension and its complications. Measurement of blood pressure in children and adolescents is needed to detect whether there is a tendency for hypertension in children and adolescents. The management of hypertension in children and adolescents can reduce the prevalence of hypertension in adulthood. This study aims to analyze the risk factors of Behavioral Risk Factors for Prevention of Hypertension in Adolescents in the Work Area of ​​the Mendahara Public Health Center, Tanjung Jabung Timur Regency 2019. This study uses a quantitative approach with a survey research type with a cross sectional design with 117 adolescents in the working area of ​​the Puskesmas. The treasurer is 13-18 years old. The sampling technique is random sampling. Data collection used a questionnaire and was carried out in August 2020. The results showed that there was a significant relationship between behavioral risk factors and efforts to prevent adolescent hypertension in the work area of ​​Mendahara Public Health Center, Tanjabtim Regency ((p <0.05). The results of this study are expected to be a reference for the Puskesmas Treasurer for early detection of the risk of hypertension in adolescents in an effort to prevent hypertension in adulthood